Public Finances and Fiscal Policy at A Crossroad ͵- What Is Next? - Trenovski, Borce (Konrad Adenauer Foundation, Republic of Macedonia/ Institute for Democracy “Societas Civilis, 2017)
Owing to the global economic crisis and the European debt crisis, the necessity of sustainable public fi nances and the need for creati ng a balance between shortterm stabilizati on objecti ves and long-term fi scal sustainability have become urgent issues. In such a situati on when public debts increase rapidly, economic growth is uncertain and confi dence in the internati onal fi nancial markets is sti ll shaken, questi ons related to public fi nances and fi scal sustainability have become signifi cant, and are hence the subject of numerous analyses, studies and books. This is a parti cularly important issue for the EU member states and, all the more, for the countries planning to integrate into the EU, since it has shown that in case of global economic disrupti ons, the fi scal policy is the fi rst “stumbling block” to sustainable macroeconomic stability of the EU. Regarding this global Trenovski Borce PUBLIC FINANCES AND FISCAL POLICY AT A CROSSROAD ͵ WHAT IS NEXT? УДК: 336.02:338.124.49497.7) 336.1:338.124.4(497.7) Изворна научна статија “What can be added to the happiness of a man who is in health, out of debt, and has a clear conscience?” Adam Smith 42 POLITICAL THOUGHT ͳ 53 JUNE 2017 trend, the Republic of Macedonia, a small and open economy, has not been left aside. The strong fi scal expansion in the country in the last several years has put its fi scal sustainability to a test, considering the fast increase of indebtedness. Taking into considerati on the great signifi cance of fi scal sustainability for the macroeconomic stability of the country, this paper focuses on the public fi nances, fi scal policy and fi scal sustainability of Macedonia, given the latest economic disturbances: the global crisis and the following period. Public fi nances and the directi on of fi scal policy will be analyzed by elaborati ng the trends in the main fi scal variables and the previous empiric research in order to demonstrate the need for adjustment, change of course and increased effi ciency of fi scal policy. This is parti cularly important in view of the pace of the debt increase, its structure, as well as fi scal policy effi ciency which are among the main indicators for assessment of Macedonia`s stability on the path to the EU.